Measurements for static shape control optimization of silicon mirror using nonlinear piezoceramic actuators. (1st March 2023) - Sumit; Kane, S R; Ganguli, Tapas; Shukla, Rahul
Abstract: In this paper, experimental study for shape control of silicon mirror is done by nonlinear piezoceramic actuator. A piezoelectric unimorph-based silicon mirror (PUSiM) is fabricated using APC 850 piezoceramic for shape control analysis. The piezo response function of all the actuators and profile of PUSiM are measured by confocal sensor at various applied electric fields to verify the nonlinearity of piezoceramic actuator. For comparison, electromechanical coupled finite element model of PUSiM is developed. Recently proposed iterative piezo response function-based optimization is used to calculate the electric field of piezoceramic actuators to achieve the target elliptical profile of PUSiM. At optimum voltage the achieved profile of PUSiM is quite close to the target elliptical profile with 193 nm root-mean-square error. Knowing the nonlinearity inherent in the piezoceramic actuators at high voltages the proposed measurement technique is a way forward for the shape control of structures and deformable mirrors.